Los objetivos de desarrollo del milenio. Algunos apuntes críticos - Echart Muñoz, Enara; Puerto Sanz, Luis Miguel (Revista Española de Desarrollo y Cooperación, 2023)
The following pages are devoted to revise, from a critical perspective, the approach, weaknesses and difficulties related to the Millennium Development Goals (MDG) as we know them. To start with, the article makes a set of general observations illustrated with examples taken from the goals themselves, their targets and indicators. The article ends up with an in-deep review of some of the MDG, especially number eight focused on developing a global partnership for development.